Biology of Spodoptera frugiperda (J.E.Smith) (Lepidoptera Noctuidae) on rice and different corn varieties - Agravante, Anthony S.; Alviar, Karen B.; Ramirez, Analiza Henedina M.; Yap, Sheryl A. (2023)
Rice and corn are one of most important crops in the Philippines. Several insect pests contribute to the losses and low yield of these crops. The fall armyworm (FAW), Spodoptera frugiperda (J.E. Smith) was reported recently to cause economic damage to corn. Also, this insect consists of two genetically differentiated strains, the corn strain and the rice strain. This study was conducted under laboratory conditions to evaluate the biological parameters of FAW on rice and different corn varieties. Newly hatched larvae were fed open pollinated variety (OPV), traditional variety, Macho F1 (hybrid), NK 6410 (genetically modified organism), and rice variety, RC 226. Duration of larva, prepupal, pupal, and larva-adult period, pre-oviposition, oviposition, and post-oviposition period, number of egg mass, fecundity, sex ratio, and survivability of larva to adult of different crops were evaluated. The results showed that the duration of development from egg to adult in Macho F1 and NK 6410 with an average duration of 24.58 and 24.66 d was significantly shorter than on OPV, traditional variety and rice variety, RC 226. The number of eggs laid by females reared on Macho F1, NK 6410, and OPV, with a mean of 1125.60, 1176.80, and 1049.40, respectively, were significantly greater than the traditional variety, tinigib and rice RC 226. Different corn varieties and rice did not affect the male and female ratio, longevity, and survivability. The results of this study will provide insights into formulating management strategies for fall armyworm.
Keywords: Armyworms; Rice varieties; Corn varieties